Ekstrakurikuler Jurnalistik untuk Mengembangkan Tulisan Siswa dan Keterampilan Berpikir Kritis - Esirosa Annashr Alinssan (Nur Science Institute, 2023)
Background: This study explores the implementation of journalism extracurricular activities in elementary education as a means to foster students’ writing and critical thinking skills. The research focuses on the journalism program at SD Muhammadiyah 1 Ketelan Surakarta, which serves as a model for integrating literacy development into extracurricular practices. Purpose: The aims of this research are to describe the implementation of journalism extracurricular activities, examine the process of developing students' writing and critical thinking skills through these activities, and identify the obstacles and solutions encountered during implementation. Method: A descriptive qualitative method with a case study design was used. Data were collected through observations and in-depth interviews involving eight informants consisting of teachers and students. Data were analyzed through data reduction, data display, and conclusion drawing. The credibility of the data was ensured through triangulation of techniques and sources. Results: The study revealed that the journalism extracurricular activities were implemented with clear planning, objectives, structured execution, and formative assessment. Students’ writing skills were developed through various activities such as writing short stories, personal narratives, and news clippings using step-by-step writing stages. Critical thinking skills were fostered through tasks that involved analyzing information and expressing ideas coherently in writing. Key obstacles included the diversity of student abilities and inconsistent writing proficiency. Solutions included personalized teacher support, motivational strategies, and selective grouping of students. Implications: The findings highlight that journalism extracurricular activities have strong potential to support literacy and critical thinking development in primary school students. With adequate planning, supportive mentorship, and contextual learning experiences, such programs can serve as effective platforms for cultivating essential 21st-century skills.